2020
DOI: 10.1002/jwmg.21846
|View full text |Cite
|
Sign up to set email alerts
|

Will Lynx Lose Their Edge? Canada Lynx Occupancy in Washington

Abstract: Populations of species located at southern range edges may be particularly vulnerable to the effects of climate change as warming temperatures and subsequent changes to ecosystems exceed speciesspecific tolerances. One such species is Canada lynx (Lynx canadensis), a cold-adapted mesocarnivore that maintains a large core population in Alaska, USA, and Canada but exists within several peripheral populations in the contiguous United States. Increases in temperature, declines in snow pack, and climateinfluenced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Our study area had a mean annual temperature ranging from −1°C to 12°C (Table A1), suggesting that snow‐ice feedback might influence warming patterns in lynx habitat, resulting in faster warming and decreased habitat suitability. King et al (2020) found a similar susceptibility to changes in temperature and snow pack for the persistence of Canada lynx at their range periphery in Washington.…”
Section: Discussionmentioning
confidence: 88%
“…Our study area had a mean annual temperature ranging from −1°C to 12°C (Table A1), suggesting that snow‐ice feedback might influence warming patterns in lynx habitat, resulting in faster warming and decreased habitat suitability. King et al (2020) found a similar susceptibility to changes in temperature and snow pack for the persistence of Canada lynx at their range periphery in Washington.…”
Section: Discussionmentioning
confidence: 88%
“…ILBT, 2013; Mote, 2003;Stoelinga et al, 2010). These shifts may have serious deleterious effects on ranges of cold-adapted species (King et al, 2020), while increasing temperature and decreases in snow cover may open more habitat up to more warm-adapted TA B L E 5 Results of conditional two-species occupancy models for six carnivore species pairs in northeastern Washington. The influence of spatial grain on interspecific interactions between dominant-subdominant pairs.…”
Section: Discussionmentioning
confidence: 99%
“…significant reductions in snow depth within Washington; ILBT, 2013; Mote, 2003; Stoelinga et al., 2010). These shifts may have serious deleterious effects on ranges of cold‐adapted species (King et al., 2020), while increasing temperature and decreases in snow cover may open more habitat up to more warm‐adapted species (e.g. cougars, coyotes, bobcats and black bears; Hansen et al., 2001; ILBT, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty in camera‐trap datasets is often ignored. Even species with otherwise obvious distinguishing characteristics can be misidentified by experts if photograph quality is poor or odd angles are captured, yet researchers rarely report how mediocre a photograph must be or the confidence of the identification necessary to merit removal from the dataset (King et al., 2020). Meek et al.…”
Section: Discussionmentioning
confidence: 99%